Sources and health consequences of marital divides: Filipino wives in intercultural marriages - Jabar, Melvin A. (Animo Repository, 2005)
Intercultural marriage in the Philippines has long been an ongoing phenomenon. Yet, studies on this subject remain scant. In particular, the health consequences of marital conflicts in such marriage are hardly investigated. Hence, this study aimed to investigate the experiences of marital conflicts among 15 Filipino wives married to foreign spouses from the provinces of Misamis Oriental and Camiguin. The study utilized qualitative in-depth interviews to examine the sources of marital conflict, the types of conflict experienced, and the health effects of these conflicts on women and their children. The study has revealed that the sources of marital conflicts included personality/attitudinal clashes, economic-related issues, differences in cultural practices, differential gender role expectations and behavior, and communication problems. While cultural differences were a source of conflict these were not as influential as personality/attitudinal clashes and economic-related issues. In general, the marital discords experienced by the Filipino wives were non-violent in nature, hence their health consequences were mild. Health problems due to marital conflicts were also temporary and manageable, thus the wives found them to have minimal effects on their over all well-being. The lighter nature and manageability of the conflicts have spared the wives and their children of grave adverse effects.